Perfil farmacológico do tipo antidepressivo do composto 3-(4-fluorofenilselenil)-2,5 difenilselenofeno: envolvimento do sistema serotoninérgico - Gai, Bibiana Mozzaquatro (2011)
Depression is a serious, recurrent and incapacitating psychiatric condition with a heavy social burden. The pharmacological approach to this disorder employs therapy with antidepressant drugs, which have side effects and numerous limitations. In view of the promising pharmacological properties of containing-selenium molecules, this study evaluated the effect of 3-(4-fluorophenylselenyl)-2,5-diphenylselenophene (DPS) in the mouse forced swim test (FST) and tail suspension test (TST), two models predictive of depressant activity. Since serotonin (5-HT) plays an important role in the pathophysiology of depressive disorders, the involvement of serotonergic system and 5-HT receptors in the action caused by DPS was studied. The antidepressant-like action of combined treatment with subeffective doses of both DPS plus paroxetine, a selective serotonin reuptake inhibitor (SSRI) was investigated. Further, we verified the possible mechanism responsible for antidepressant-like action of DPS. The results showed that DPS (50 and 100 mg/kg, p.o.) significantly reduced the immobility time during the FST and TST, without accompanying changes in ambulation when assessed in the open-field test. The anti-immobility effect of DPS (50 mg/kg, i.g.) in the FST was prevented by pretreatment of mice with pCPA (p-chlorophenylalanine; an inhibitor of 5-HT synthesis, 100 mg/kg, i.p., once a day for 4 consecutive days,), WAY 100635 (N-[2- [4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-N-2-pyridinylcyclohexane carboxamide; 0.1 mg/kg, s.c., a selective 5-HT1A receptor antagonist), ritanserin (1 mg/kg, i.p., a 5-HT2 receptor antagonist) or ondansetron (1 mg/kg, i.p., a 5-HT3 receptor antagonist). Combined treatment with paroxetine and DPS reduced the immobility time in the FST. DPS at the dose of 50 mg/kg did not produce any change in the cerebral activity of monoamine oxidase subtypes (MAO-A or MAO-B). DPS at the dose of 50 mg/kg inhibited significantly 5-HT uptake in mouse brain synaptosomes. These results suggest that DPS produced an antidepressant-like action in the mouse FST and TST and this action seems most likely to be mediated through an interaction with serotonergic system, particularly by 5-HT reuptake inhibition.